The use of generative artificial intelligence for teaching English to future physical culture specialists - Puzatyh, A.N.; Puzanov, A.P. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to develop didactic content for English language classes using artificial intelligence technologies that increase the engagement of future physical education specialists in the learning process. Methods and structure of the study. The materials used included lesson plans created with the help of neural networks based on generative artificial intelligence, such as Perplexity, DeepSeek, and the specialised web application Character.ai, which helps develop oral and written foreign language communication skills. The study was conducted at the Institute of Physical Culture, Sports and Life Safety of the I.A. Bunin Yelets State University in the 2023-2025 academic years in English classes for 1st and 2nd year bachelor's degree students in the following areas of study: 49.03.01 Physical Education, 49.03.02 Physical Education for People with Health Disabilities (Adaptive Physical Education). A total of 62 students participated in the experiment. Results and conclusions. Several lesson plans have been developed using neural networks on the following topics: ‘My hobby,’ ‘My future profession,’ and ‘Sport in my life.’ A specialised chatbot has been developed in the Character.ai application to improve the foreign language communication skills of physical education students.